Advances in Human Factors in Robots and Unmanned Systems Proceedings of the AHFE 2018 International Conference on Human Factors in Robots and Unmanned Systems, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Chen, Jessie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book focuses on the importance of human factors in the development of safe and reliable unmanned systems. It discusses current challenges such as how to improve the perceptual and cognitive abilities of robots, develop suitable synthetic vision systems, cope with degraded reliability in unmanned systems, predict robotic behavior in case of a loss of communication, the vision for future soldier-robot teams, human-agent teaming, real-world implications for human-robot interaction, and approaches to standardize both the display and control of technologies across unmanned systems. Based on the AHFE 2018 International Conference on Human Factors in Robots and Unmanned Systems, held on July 21-25, 2018, in Orlando, Florida, USA, this book fosters new discussions and stimulates new advances in the development of more reliable, safer, and highly functional devices for carrying out automated and concurrent tasks.
Keywords: Computational intelligence; Control engineering; Robotics; Automation; Psychology, Experimental; User interfaces (Computer systems).; Human-computer interaction; Computational Intelligence; Control, Robotics, Automation; Experimental Psychology; User Interfaces and Human Computer Interaction